Konseling trauma oleh Ikatan Konselor Indonesia (IKI) untuk korban bencana alam gempa bumi (studi di Kabupaten Pidie Jaya) - Nur’aini Safitri; Imalatul Khairat (Ikatan Konselor Indonesia (IKI))
The earthquake that occurred on December 7, 2017 in Pidie Jaya leaving a deep sorrow for the victims (children and parents) even many traumatized victims (Post Traumatic Stress Disorder). This research is a descriptive qualitative. Data analysis technique used is the method of triangulation data. The results of this study are: (a) trauma counseling activities carried out by the Indonesia Counselors Association for victims of the earthquake in Pidie Jaya format consists of four activities, namely the format of individual, group, classical, and pitch. Activity trauma counseling for victims that service individual counseling, relaxation, art theraphy, play therapy, Self Report and Sharing, SEFT (Spiritual Emotional Freedom Technique) and NLP (Neoro Linguistic Programming), (b) The damage caused to the victims of natural disasters earthquake after receiving counseling traumatized victims (target service) benefited greatly from counseling services that have been provided by a team of IKI such as being able to control your emotions, overcome panic / fear that is in itself after the earthquake, can think positively and take lessons from the disaster, can smile back/no sadness, and can rise to reorganize/planning back a better life again in the future after the earthquake, (c) public perception of counseling trauma that has been implemented by IKI is very nice , creative, useful and much needed by the community, and (d) the counselor is a dignified profession